2021
DOI: 10.1039/d0sc06837c
|View full text |Cite
|
Sign up to set email alerts
|

Translational dynamics of a non-degenerate molecular shuttle imbedded in a zirconium metal–organic framework

Abstract: An unsymmetrical molecular shuttle was incorporated into the octahedral cavities of a Zr(iv) MOF. 13C SSNMR showed that the presence of mesitylene in the pores results in an increase in the barriers for the thermally driven motion of the macrocycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…In the current study, we focused on the shuttling rate due to the embedding in the MOF. The small differences (underestimations) with respect to the measured data might thus be due to the absence of a solvation environment in the atomistic simulations, which is in line with experimental observations (63).…”
Section: Dynamics Of the Embedded Mbrssupporting
confidence: 85%
“…In the current study, we focused on the shuttling rate due to the embedding in the MOF. The small differences (underestimations) with respect to the measured data might thus be due to the absence of a solvation environment in the atomistic simulations, which is in line with experimental observations (63).…”
Section: Dynamics Of the Embedded Mbrssupporting
confidence: 85%
“…The mechanics of motion in solids has been attracting increasing interest from the perspective of designing organized molecular rotors, motors, and machines, the goal being to control their functions and properties, such as the commutation of light into mechanical work, dielectric and optical properties, and ferroelectricity. Different strategies have been addressed for the targeted construction of dynamic materials, including the use of self-assembly principles, host–guest compounds, and hybrid materials. …”
Section: Introductionmentioning
confidence: 99%
“…By incorporating a non-degenerate molecular shuttle as an organic linker, the same research group reported the preparation of zirconium-based MOF UWDM-11. 148 The bistable molecular shuttle is constituted by a thread having two different benzimidazole stations, one functionalized with two bromine atoms and another with two pendant phenyl-carboxylate moieties, encircled by a [24]crown-8 cyclic component. The X-ray single-crystal structure of the interlocked ligand shows that the wheel preferentially surrounds the station attached to the phenyl dicarboxylate groups (Fig.…”
Section: Ph-and Solvent-responsive Morfsmentioning
confidence: 99%